Soil water content and emergence time control seedling establishment in three co-occurring Mediterranean oak species - Urbieta, Itziar R.; Pérez-Ramos, Ignacio M.; Zavala, Miguel A.; Marañón, Teodoro; Kobe, Richard K. (Canadian Journal of Forest Research, 2008)
Tree species can differ in their responses to resource availability during the critical phase of establishment, which could influence forest dynamics. In Mediterranean forests, most of the attention has focused on the effects of shade and summer drought on seedling survival, but little is known about the effect of autumn to spring rains on earlier stages of recruitment. A sowing experiment was set up along natural light and water gradients with three co-occurring oak species (Quercus suber L. (cork oak), Quercus canariensis Willd. (Algerian oak), and Quercus pyrenaica Willd. (Pyrenean oak)) that show limited natural regeneration in southern Spain. Recruitment stages were monitored for 1 year. Models of seed germination, seedling emergence, and seedling survival as well as of overall recruitment patterns were developed as functions of light, soil moisture, and soil compaction. The influence of intraspecific variation in seed mass and emergence time were also tested. Excess soil water levels during the winter reduced germination and emergence and lengthened time to emergence (in waterlogged open areas), which in turn decreased seedling survival during the dry season. Seedlings from larger seeds were more likely to germinate and emerge. The results suggest that temporal and spatial variability of soil water content, mediated by emergence time and seed size, play a crucial role in the regeneration dynamics of Mediterranean oak forests.
doi: 10.1139/X08-089doi: 10.1139/X08-089The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: Mediterranean oak species; Modelling; seed germination; seedling emergence; seedling survival (voyant); Soil water content

Soil water content and emergence time control seedling establishment in three co-occurring Mediterranean oak species (Canadian Journal of Forest Research, 2008)
Tree species can differ in their responses to resource availability during the critical phase of establishment, which could influence forest dynamics. In Mediterranean forests, most of the attention has focused on the effects of shade and summer drought on seedling survival, but little is known about the effect of autumn to spring rains on earlier stages of recruitment. A sowing experiment was set up along natural light and water gradients with three co-occurring oak species (Quercus suber L. (cork oak), Quercus canariensis Willd. (Algerian oak), and Quercus pyrenaica Willd. (Pyrenean oak)) that show limited natural regeneration in southern Spain. Recruitment stages were monitored for 1 year. Models of seed germination, seedling emergence, and seedling survival as well as of overall recruitment patterns were developed as functions of light, soil moisture, and soil compaction. The influence of intraspecific variation in seed mass and emergence time were also tested. Excess soil water levels during the winter reduced germination and emergence and lengthened time to emergence (in waterlogged open areas), which in turn decreased seedling survival during the dry season. Seedlings from larger seeds were more likely to germinate and emerge. The results suggest that temporal and spatial variability of soil water content, mediated by emergence time and seed size, play a crucial role in the regeneration dynamics of Mediterranean oak forests.
doi: 10.1139/X08-089